A Framework for the Improvement of Frugal Design Practices - Ravindra Singh; Sumedha Seniaray; Prateek Saxena (Designs, 2020)
Current frugal design practice is focused on the cost reduction of the product. Despite advancements in the domain of frugal Innovation, it is not systematized to develop products for all sets of users, including marginalized society. Many design researchers and engineers now dedicate time and knowledge to producing practical solutions to enhance the quality of life of the marginal community. The approach currently being adopted restricts the development of products intended for all segments of the users. In this paper, cumulative frequency distribution analysis and the Relative Importance Index is used to identify the essential attributes, which contribute to delivering actual frugal products in terms of functionality, usability, performance, affordability, accessibility, aesthetics, and robustness. The framework is beneficial to eradicate the discriminatory effect of being labeled as “Jugaad” users.